2008
DOI: 10.1152/jn.90355.2008
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Frontoparietal Control System Revealed by Intrinsic Functional Connectivity

Abstract: Two functionally distinct, and potentially competing, brain networks have been recently identified that can be broadly distinguished by their contrasting roles in attention to the external world versus internally directed mentation involving long-term memory. At the core of these two networks are the dorsal attention system and the hippocampal-cortical memory system, a component of the brain's default network. Here spontaneous blood-oxygenation-level-dependent (BOLD) signal correlations were used in three sepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

122
1,478
9
11

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 1,712 publications
(1,620 citation statements)
references
References 93 publications
122
1,478
9
11
Order By: Relevance
“…One examined age differences in inhibition using a series of tasks that assessed the ability to inhibit prepotent responses 45 . Older adults displayed more activity in a set of dorsal PFC and parietal regions, sometimes called the dorsal attention network 46,47 , compared with younger adults. Importantly, activity in these attention-related regions correlated with better inhibition only in older adults.…”
Section: Compensation In the Older Brainmentioning
confidence: 99%
“…One examined age differences in inhibition using a series of tasks that assessed the ability to inhibit prepotent responses 45 . Older adults displayed more activity in a set of dorsal PFC and parietal regions, sometimes called the dorsal attention network 46,47 , compared with younger adults. Importantly, activity in these attention-related regions correlated with better inhibition only in older adults.…”
Section: Compensation In the Older Brainmentioning
confidence: 99%
“…We confirm previously established behavioral effects showing that at synchrony, older adults are able to resist distraction (Hasher et al, 2005;Rowe et al, 2006;Schmidt et al, 2007), and crucially for the first time, demonstrate that to do so they activate a set of attentional control regions recruited by younger adults. Older adults tested in the afternoon during their off-peak time of day showed both a behavioral and neural decrement, as they are not as able to resist distraction nor draw on the appropriate brain regions as their young peers or age mates tested in the morning.The cognitive control network, which includes lateral and rostral prefrontal cortices and the inferior parietal lobules, has recently risen to prominence as a possible master "switch," controlling access to the default and the dorsal attention network s. Recent work has suggested that not only is the control network interposed between the dorsal attention and default networks (Vincent et al, 2008), but it functionally modulates the relationship between them during tasks (Spreng et al, 2010), and at rest is affected by endogenous levels of dopamine (Dang et al, 2012).The idea that older adults have difficulty regulating activity in control regions, and by implication in modulating a putative network "switch", agrees with other literature suggesting that this group also has difficulty modulating functional connections between various regions comprising both task-positive and default networks (Lustig et al, 2003;Persson et al, 2007;Grady et al, 2010). There is also evidence that older adults may have difficulty suppressing the default network when on task, suggesting that they may be more prone to interference from mind-wandering, or reflecting on autobiographical memories during an experiment (Grady et al, 2006;Park et al, 2010).…”
mentioning
confidence: 99%
“…A plethora of previous studies on adults have confirmed the importance of these very same cortical regions for executive functioning. It is commonly held that a “frontoparietal control network” is crucial to all executive processes (Badre & D'Esposito, 2007; Fedorenko et al., 2013; Vincent et al., 2008). In addition to this shared brain circuitry, brain imaging studies have repeatedly observed a differential functional organization or unique response patterns within shared brain regions between different executive control components (Marklund et al., 2007; Miyake et al., 2000; Stiers, Mennes, & Sunaert, 2010; Wager & Smith, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of brain activity, the different executive tasks were expected to recruit regions in parietal cortical regions and in lateral and medial prefrontal regions, as demonstrated by our earlier work (Moisala et al., 2015, 2017). Functional connectivity between these frontoparietal nodes was expected to be similar irrespective of the specific demands of each task type, as the components of this “frontoparietal control system” (Vincent, Kahn, Snyder, Raichle, & Buckner, 2008) are co‐active in a wide variety of task domains (Duncan, 2010; Fedorenko, Duncan, & Kanwisher, 2013) and are known to subserve a variety of executive functions (Niendam et al., 2012). Moreover, age‐related differences in cortical activity and functional connectivity overlap between different executive task types were of special interest.…”
Section: Introductionmentioning
confidence: 99%